Integrating corporate sustainability and sustainable development goals: Towards a multi-stakeholder framework - Avinash Pratap Singh; Zillur Rahman (Cogent Business & Management, 2021)
The United Nations Sustainable Development Goals (SDGs) are a basket of major global challenges. No business is untouched by the challenges presented by the SDGs. The SDGs are well connected with the three pillars of corporate sustainability. This research paper has two unique properties: first, it uses a stakeholder approach to establish the organic linkages between the triple bottom line (TBL) approach and SDGs. India is committed to the SDGs of the United Nations. Indian public and private corporations can play a key role in India's commitments to achieving SDGs by 2030. The second objective of this study is to examine the alignment of the top 100 Indian companies with the SDGs based on quantitative content analysis. The proposed SDG-TBL framework contributes to advance theoretical and practical understanding of the factors influencing the adoption of SDGs by businesses. This article also offers implications for researchers and practitioners.
Keywords: 650; Sustainable development goals (SDGs); triple bottom line (TBL); stakeholder engagement; corporate reporting; corporate sustainability